An Analysis of the Relationship Between Ritual Worship Intensity (Ibadah Mahdah) and Consumer Preferences for Halal-Certified Products - Bambang Saiful Ma'arif; Reny Rian Marlina; Irfan Safruddin (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This persuasive communication study examines the relationship between levels of religiosity and preferences for halal products within the context of evolving contemporary communication. The research highlights the interconnection between religiosity, persuasive da’wah communication, and public tendencies in selecting and consuming halal-certified products. This study employs a quantitative methodology using proportional sampling techniques, involving 120 respondents, and is analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the validity, reliability, and structural model hypotheses. Findings indicate that 78.9% of respondents perform obligatory prayers (shalat fardhu) very frequently, 88.9% fast during Ramadan regularly, and 55% rarely read the Qur’an. The total score of ritual worship (ibadah mahdah) reached 2,071 out of a maximum of 2,725, reflecting a high level of religiosity. The Likelihood Ratio test reveals a significant relationship between obligatory prayer and both the rationale for choosing halal products (p = 0.0054) and the ability to verify halal status (p = 0.0199). Observing obligatory fasting shows significant correlation with halal product preferences (p = 0.0037) and the boycott of Israeli products (p = 0.0196). Voluntary fasting is significantly related to the duration of halal product usage (p = 0.0020) and halal verification (p = 0.0295). Conclusion: A high level of ritual worship (ibadah mahdah) significantly influences preferences for halal products, reinforcing religious awareness and conscientious consumption in accordance with Islamic teachings.